Moroccan judgment exequatur on divorce and maintenance claims: subpoena, definitive judgment and provisional execution (Girona Provincial Court - Order of 08/10/2019) - Vargas Gómez-Urrutia, Marina (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This note is aimed at the Order of the Provincial Court of Girona of October 8, 2019. The Court adequately contextualizes the legal regime applicable to the recognition and enforcement of a Moroccan divorce and maintenance obligation and examines, in the light of the claims invoked, the conditions for its granting as well as the possibility of provisional execution even if it has not been proven that the sentence is final.